Electoral Behavior in The Electability of Presidential and Vice Presidential Candidates in The 2019 Elections - Ferdhiman P Bariguna; Affan Sulaeman; Wawan Budi Darmawan (Universitas Pancasakti Tegal, 2021)
This study aims to explain how factors, such as social and religious status, candidate figures, party identity, social and conventional media interactions, issue and program orientation, support of influential figures, and funds affect voter behavior in the 2019 Presidential and Vice Presidential Elections, to be precise in Ibun District. The study of voting behavior was developed because party identification or party loyalty did not have a strong influence, while what happened was that there were social divisions that had strong ties to voter behavior. An interesting phenomenon occurred in Ibun Subdistrict since there was a significant change in the number of voters in the 2014 presidential election where Prabowo received more votes than Jokowi, while in 2019, Jokowi received more votes than Prabowo. The research method in this research was explanatory quantitative research methods by collecting data from the results of questionnaires and documentation. The structural equation model (SEM) analysis method was also carried out to determine the effect of the dependent variable on the independent variable. Based on the findings obtained from this research, the researcher found that four variables greatly influenced the electability of candidates, namely media, the intensity of volunteer visits, religion, and role models. Psychological, sociological, and rational factors map voter behavior so that this can be applied in Ibun Subdistrict. The psychological aspects are represented by the media and role models; the sociological aspect represented by religion, while the rational aspect is represented by the figure of the candidate. Therefore, to increase the electability of candidates, they should imoprove positive image in the media, the intensity of volunteer visits, social piety from religious factors, and relationships with local community leaders.